Tras la estela del arte : reflexiones en torno a la obra de Paco Lagares - Calvente, Pablo García (2019)
The work of Paco Lagares, demonstrates a sublime technical style supported by a trajectory beginning in the early 1970s. It skillfully unwraps the disperse disciplines of drawing, painting and sculpture with fluidity expressed in a praisworthy narrative wherein echoes of classical naturalism are interwoven with dexterity in these visual arts. They include drawings that emulate his love for plant forms to the strength expressed by his sculptures —ranging from the classic to the contemporary— or his paintings, exhibiting an accomplished compositional sense typical of theatrical staging